$2.00 a day : living on almost nothing in America - Edin, Kathryn, 1962- (Houghton Mifflin Harcourt, 2015)
"A revelatory account of poverty in America so deep that we, as a country, don't think it exists. Jessica Compton's family of four would have no cash income unless she donated plasma twice a week at her local donation center in Tennessee. Modonna Harris and her teenage daughter Brianna in Chicago often have no food but spoiled milk on weekends. After two decades of brilliant research on American poverty, Kathryn Edin noticed something she hadn't seen since the mid-1990s -- households surviving on virtually no income. Edin teamed with Luke Shaefer, an expert on calculating incomes of the poor, to discover that the number of American families living on $2.00 per person, per day, has skyrocketed to 1.5 million American households, including about 3 million children. Where do these families live? How did they get so desperately poor? Edin has "turned sociology upside down" (Mother Jones) with her procurement of rich -- and truthful -- interviews. Through the book's many compelling profiles, moving and startling answers emerge. The authors illuminate a troubling trend: a low-wage labor market that increasingly fails to deliver a living wage, and a growing but hidden landscape of survival strategies among America's extreme poor. More than a powerful expose, $2.00 a Day delivers new evidence and new ideas to our national debate on income inequality. "--